Une approche d’ingénierie cognitive pour la gestion intégrée de zones côtières : le cas d’un barrage sur un estuaire. - Caroline Blanche; Evelyne Goubert; Thierry Morineau (VertigO)
The territory of the Vilaine estuary located in the south of Brittany (France) represents an ecosystem that involves socio-economical and environmental interests. Since the building of a dam, this territory decreases as the function of the silting up, increasing the risk of use conflicts. The resort to Cognitive Engineering as a methodological framework aims at proposing a new approach in the area of integrated management. This framework looks for taking into account the ecosystem ecology within the instrumental practices of actors. In addition to the description of a technical system in interaction with an ecosystem through a new viewpoint, this analysis should allow for proposing some actions to optimise the dam functioning.